Assessment of the phytochemical constituents and antioxidant activity of a bloom forming microalgae Euglena tuba - Chaudhuri, Dipankar (BioMed Central, 2014)
BACKGROUND: Unstable generation of free radicals in the body are responsible for many degenerative diseases. A bloom forming algae Euglena tuba growing abundantly in the aquatic habitats of Cachar district in the state of Assam in North-East India was analysed for its phytochemical contents, antioxidant activity as well as free radical scavenging potentials. RESULTS: Based on the ability of the extract in ABTS(•+) radical cation inhibition and Fe(3+) reducing power, the obtained results revealed the prominent antioxidant activity of the algae, with high correlation coefficient of its TEAC values to the respective phenolic and flavonoid contents. The extract had shown its scavenging activity for different free radicals and 41.89 ± 0.41 μg/ml, 5.83 ± 0.07 μg/ml, 278.46 ± 15.02 μg/ml and 223.25 ± 4.19 μg/ml were determined as the IC(50) values for hydroxyl, superoxide, nitric oxide and hypochlorous acid respectively, which are lower than that of the corresponding reference standards. The phytochemical analysis also revealed that the phenolics, flavonoids, alkaloids, tannins and carbohydrates are present in adequate amount in the extract which was confirmed by HPLC analysis. CONCLUSIONS: The results showed that 70% methanol extract of the algae possesses excellent antioxidant and free radical scavenging properties.